2019
DOI: 10.33317/ssurj.v8iii.92
|View full text |Cite
|
Sign up to set email alerts
|

Human Heart Disease Prediction System Using Data Mining Techniques

Abstract: — Prediction of heart disease is a big concern now a days because everyone is busy and due to heavy load of work people do not give attention to their health. To diagnose a disease is a big challenge. The issue is to extract data that have some meaningful knowledge. For this purpose, data mining techniques are used to extract meaningful data. Decision Tree and ID3 are used to predict heart diseases. Many researchers and practitioners are familiar with prediction of heart diseases and wide range of techniques i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many research groups have made significant contributions in this area, and some of their approaches are highlighted here. J. Thomas et al [1] utilized data mining techniques and applied K-nearest neighbor, neural network, naive Bayes, and decision tree algorithms to predict heart disease risk rates. M. Ashu Sharma et al focused on cleaning and preprocessing the dataset and found that neural networks yielded high precision in heart disease prediction [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many research groups have made significant contributions in this area, and some of their approaches are highlighted here. J. Thomas et al [1] utilized data mining techniques and applied K-nearest neighbor, neural network, naive Bayes, and decision tree algorithms to predict heart disease risk rates. M. Ashu Sharma et al focused on cleaning and preprocessing the dataset and found that neural networks yielded high precision in heart disease prediction [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The developed ECG monitoring device modules on PCB and attachable electrodes are shown in Figure 9 weighing a total of 580 grams. It is to note that the transformer weight alone weighs 350 grams, which can be replaced with a wave rectifier and a chopper circuit [20][21][22][23][24][25][26].…”
Section: G Serial To Usb Communicationmentioning
confidence: 99%